RETRACTED: Khan et al. Poly (N-vinylcaprolactam-grafted-sodium alginate) Based Injectable pH/Thermo Responsive In Situ Forming Depot Hydrogels for Prolonged Controlled Anticancer Drug Delivery; In Vitro, In Vivo Characterization and Toxicity Evaluation. Pharmaceutics 2022, 14, 1050 - Samiullah Khan; Muhammad Usman Minhas; Muhammad Tahir Aqeel; Ihsan Shah; Shahzeb Khan; Mohsin Kazi; Zachary N. Warnken (MDPI AG, 2024)
The journal retracts the article, "Poly (N-vinylcaprolactam-grafted-sodium alginate) Based Injectable pH/Thermo Responsive In Situ Forming Depot Hy-drogels for Prolonged Controlled Anticancer Drug Delivery; In Vitro, In Vivo Characterization and Toxicity Evaluation" [...]